Application of the Design of Experiment (DoE) methodology to optimize the chewable tablet compression process in a pharmaceutical industry (Research, Society and Development, 2020)
The tablet compression step in the pharmaceutical industry is a complex process, with numerous variables and response parameters. During the life cycle of a drug, the product may undergo changes that may affect tableting process and a possible need for performance gains in the tablet machine, such as supplier switching or batch augmentation, respectively. The present study aims to optimize the tableting process of a line product aiming at increasing speed (tablets / hour). The work will be conducted using the Design of Experiments (DoE) methodology in order to identify and correlate the critical parameters during the process that affect the maintenance of the compression speed. In order to do this, we applied the DoE methodology recommended in the Quality by Design (QbD) and described in the ICQ8 guide, to evaluate the interactions of the parameters with each other and to indicate the optimum conditions for the compression of the product. In order to support our experiments, we test the time of disintegration, medium hardness and variation of hardness, average weight and friability. As a result, we obtained that several quality attributes of disintegration and friability did not generate a significant model, but we were able to establish correlations between Fill-O-Matic (FOM) velocity and main compression force in the responses of variation of weight, hardness and mean hardness.